Cats and Dogs: Two Neglected Species in this Era of Embryo Production in Vitro?. (June 2014) - Van Soom, A; Rijsselaere, T; Filliers, M
Contents: During the last decades, in vitro fertilization (IVF) has become a routine technique in most domestic animals. However, in the dog the technique has lagged behind, with to date not a single pup born after IVF. In cats, healthy kittens have been born, but in fewer numbers than in cattle and horses. In pet animals, research in reproduction has mainly been focused on contraception, although recently, the introduction of new drugs especially marketed for cats and dogs will probably expand fertility research in carnivores towards the previously neglected area of assisted reproduction. In particular, the dog remains a real challenge for the reproductive biologist, due to the low meiotic capacity of canine follicular oocytes. In cats, oocyte maturation is less of a problem and embryo production rates comparable to those of cattle can be achieved. The domestic cat is a valuable model for endangered felids and it can even be used as a recipient for wild felid embryos. In this short review, we list some of the problems associated with the implementation of IVF in dogs and cats in relation to their reproductive characteristics, and we discuss the state‐of‐the‐art of IVF in several other domestic species such as cattle, horses and pigs.